Understanding how social norms influence access to and utilization of adolescent sexual and reproductive health services in Northern Nigeria - Taiwo, Modupe Oladunni; Oyekenu, Oluwatoyin; Hussaini, Rahinatu (Frontiers in Sociology, 2023)
Background This study explored the influence of social norms on the access and utilization of sexual and reproductive health services by adolescents. Apart from individual and environmental barriers, social norms influence contraceptive decisions and ultimately sexual and reproductive health outcomes. Social norms that shape group behavior describe acceptable standards of behavior and evoke sanctions when such behavior standards are not adhered to. Sexually active adolescents in Nigeria have a relatively low level of modern contraceptive use being influenced by social norms. Scaling up adolescent reproductive health interventions that integrate normative change for a wider impact of programs remains challenging. Methods Using data from 18 communities, 188 married and unmarried adolescents (F52% and M48%) and 69 (F37%; M63%) reference group participants were purposively sampled and participated in a social norms exploration intervention study conducted through focus group discussion and in-depth interviews between October and November 2019. The Advancing Learning and Innovation on Gender Norms (ALIGN) Social Norms Exploration Tool (SNET) was adapted for the data collection into discussion guides and vignettes. Pilot testing of the tools informed review and validation prior to actual data collection. Findings Low contraceptive uptake by adolescents was characterized by early and forced marriage in childhood; a prominent practice enshrined in social norms around girl-childchastity, family honor, and disapproval of pre-marital sex and pregnancy out of wedlock. Conclusion The understanding of harmful social norms, normative change actors, and potential norm-shifting factors for contraceptive decisions by adolescents is essential for effective adolescent sexual and reproductive health interventions for wider impact and adaptive programming in behavior change interventions for improving the access to and utilization of modern contraceptives by adolescents for improved sexual health outcomes, the attainment of the Family Planning (FP) 2030 commitment and universal health coverage policy.